PRODUKTIVITAS MODAL DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN DI KOTA SAMARINDA - Adyastuti Putri Kuswadie; Dr muliadi; juliansyah roy (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
Adyastuti Putri Kuswadie, 2019. The Effect of Capital and Labor Productivity on Economic Growth and Income Inequality in Samarinda City. This research was guided by Muliadi as supervisor I and Juliansyah Roy as supervisor II.This study aims to determine how much influence the variable Capital Productivity, Labor Productivity on Economic Growth and Income Inequality in Samarinda City using the Path Analysis tool processed in the SPSS 22 computer program. This study uses 2007 time series data -2017 obtained from the Central Statistics Agency of East Kalimantan Province.The results of this study indicate that the Capital Productivity variable has a negative and significant effect on the variable Economic Growth. While the Labor Productivity variable has a positive and significant effect on the Economic Growth variable. Capital Productivity, Labor Productivity, and Economic Growth Variables significantly influence the Income Inequality variable.